The Effect of Service Quality on Patient Satisfaction at Jampang Kulon General Hospital, West Java Province - Udriyah; D Ilham Rizkian; Ali Ridho; Alfi Maghfuriyah (International Publisher, 2022)
This research is a quantitative study that aims to determine the effect of service quality on patient satisfaction at Jampang Kulon General Hospital, West Java. This is based on the problem of several complaints by patients regarding the quality of existing services. In this study, the unit of analysis was patients at Jampang Kulon General Hospital, the population included were all patients at the Jampang Kulon General Hospital, West Java Provincial Government, from January 2021 to March 2021, a total of 1,658 patients. The sampling technique is Probability Sampling and the number of samples is 94 people. Based on the results, it can be concluded that service quality has a positive effect on patient satisfaction at the Jampang Kulon General Hospital, West Java Province with an effect of 33.98% and a regression function of Y = 14.080 + 0.555 X.